Evaluation of Medicolegal Autopsy Results of Child Hood Deaths in 1997-2001 at Adana - Arslan, Muhammet Mustafa; Kar, Hakan; Çekin, Necmi; Karanfil, Ramazan (The Bulletin of Legal Medicine, 2004)
Children become physically disabled of predictable and preventable reasons, varying in ratios from country to country. We aimed to help developing preventive medicine programs via our studies on autopsied childhood death cases at Forensic Medicine, Adana Group Administration by listing the origins, causes of death and age distribution of the cases. We presented the childhood death cases autopsied between 1997-2001 at Morgue Department of Council of Forensic Medicine, Adana Group Administration classified by years, origin of death, cause of death, gender and age groups with the table and graphics associated. We discovered 682 childhood age death cases in our study. When investigated through years and age groups, it’s seen that there’s a rising trend in overall number of cases from year to year. 0-6 age group is occupying the highest share among all death cases with 260 incidents which equals 38.12% of the total cases. As per research for origin of death among age groups, we see that 0-6 and 12-15 age groups death origins are mostly “natural”, while at 7-11 age group, origin of death is mostly “accidents” and “suicide” is the one which is significant for 16-18 age group. According to the cause of death distribution among age-groups, it’s seen decease-related deaths are common between 0 and 6 year-old infants while gunshot wounds and drowning are most common in other age groups. We believe developing and practicing regional preventive medicine strategies, created considering local dynamics will cause a significant decrease in death cases related to preventable reasons.Key words: Autopsy, childhood, death.
Keywords: autopsy; childhood; death